Analytical study of crowdsourced GLAM digital repositories. Issue 1 (5th March 2018) - Gupta, Dinesh K.; Sharma, Veerbala
Abstract : Purpose: The purpose of this paper is to find out the status/levels of using crowdsourcing in galleries, libraries, archives and museums (GLAM) around the globe and to give suggestions on how Indian GLAM can take the benefit of this global trend. Design/methodology/approach: The study is based on the analytical study of the literature available on the embracing crowdsourcing for diverse tasks with special emphasis on the efforts of GLAM domain regarding the development of digital repositories. Findings: Meticulous analysis of literature and case studies give an overview of the diverse practices of public participation/crowd collaboration in the development of digital repositories around the globe. However, Indian GLAM are far behind in adopting such practices. Practical implications: With the rapid growth in digital information and Web-based technology, GLAM around the world encourage and engage public participation in various digitization projects to enrich and enhance their digital collections and place them on the Web. However, Indian GLAM still refrain to accept and adopt such practices. Thus, this paper will encourage and motivate the Indian GLAM to enrich and enhance their collection with crowd contribution and uploading them on Web. Originality/value: This is an original paper and has great implementation value. During the study, enormous literature was available on crowd participation in various areas around the globe, as well as in India. International examples of crowd participation in GLAM creation are found in the literature; however, not sufficient evidences are found regarding crowd contribution in Indian GLAM. Hence, the paper, by presenting the evidences of crowd participation in GLAM domain, proposes the Indian GLAM to exploit the benefits of this practice for Indian digital repositories to expedite the creation and development of various national digital repositories.